2002
DOI: 10.1097/00004356-200212000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Into work, through tailored paths: a two-year follow-up of the return-to-work rehabilitation and re-employment project

Abstract: Between the years 1996 and 2000, over 2000 projects were carried out in Finland with the aim of finding innovative measures for crossing the job threshold. Among them was the Pathway-to-Work Project, which aimed at tailoring return-to-work plans for 140 middle-aged, long-term unemployed participants with various disabilities and getting half of them into work or training. This study of the Pathway-to-Work Project had two research objectives. First, to evaluate the outcomes of the return-to-work rehabilitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…These data clarify the role of the sense of coherence in coping with chronic pain and emotional distress, but question the presumed role of the sense of coherence in work re-entry of persons with long-term chronic musculoskeletal pain. In contrast, the Pathway-to-Work Project (Juvonen-Posti, Kallanranta, Eksyma, Piirainen, & Keinänen-Kiukaanniemi, 2002) found participants' distress level to decrease remarkably during rehabilitation, and their perceived competence increased, but their sense of coherence did not change.…”
Section: Intervention Researchmentioning
confidence: 80%
“…These data clarify the role of the sense of coherence in coping with chronic pain and emotional distress, but question the presumed role of the sense of coherence in work re-entry of persons with long-term chronic musculoskeletal pain. In contrast, the Pathway-to-Work Project (Juvonen-Posti, Kallanranta, Eksyma, Piirainen, & Keinänen-Kiukaanniemi, 2002) found participants' distress level to decrease remarkably during rehabilitation, and their perceived competence increased, but their sense of coherence did not change.…”
Section: Intervention Researchmentioning
confidence: 80%
“…Similarly to Stuckler et al (2009), Anderson (2009) found a positive social effect of ALMP expenditure on the dependent variables, with a stronger impact for harder-to-reach 'labour market outsiders'. At the national level, there is evidence of a positive ALMP effect on well-being for Finland (Vuori and Vesalainen 1999;Juvonen-Posti et al 2002), Germany (Behle 2005;Wulfgramm 2011), Serbia (Bonin and Rinne 2014) and Sweden (Hagquist and Starrin 1996;Korpi 1997;Strandh 2001;Röjdalen et al 2005); on health for Sweden (Westerlund Evidence from the UK et al 2004) and Spain (Ayala and Rodriguez 2013); and on social capital for Denmark (Andersen 2012). However, there is also evidence that ALMPs offer no added health and social benefits compared to open unemployment.…”
Section: The Health and Psychosocial Effects Of Unemployment And The mentioning
confidence: 99%
“…Only two earlier studies have investigated changes in SOC of the unemployed during labor market interventions. The results of a Finnish study (Juvonen‐Posti, Kallanranta, Eksyma, Piirainen & Keinänen‐Kiukaanniemi, 2002) found no change in the level of participants’ SOC, even though a decrease in psychological distress and an increase in perceived competence were observed. In a German study of Richter and Nitsche (2002), positive short‐term effects during an intervention were detected.…”
Section: Introductionmentioning
confidence: 99%